CETEAU PVD VACUUM SYSTEM IN SOFT BANGKOK CLAY: A CASE STUDY OF THE SUVARNABHUMI AIRPORT PROJECT - J. Saowapakpiboon; D. T. Bergado; S. Hayashi; J. C. Chai; N. Kovittayanon; T. P. de Zwart (Lowland Technology International, 2008)
A new improvement technique is currently applied for soft Bangkok clay combining capped PVD with vacuum pressure and embankment loading whereby the prefabricated vertical drains (PVD) are connected by PE tubes to a vacuum pump called “CeTeau PVD Vacuum System”. The method uses a surface soil layer as a sealing layer for leakage protection and there is no need to place air-tightening geomembrane sheets on the ground surface. This method has two advantages for situations of a) high air/water permeability layer exist near the ground surface, and b) combining vacuum pressure with embankment load. An actual field project combining PVD vacuum and embankment loading has just been completed. The performance data of the system during the improvement of the section EW-4, a part of the third runway of Suvarnabhumi International Airport, Thailand are presented and interpreted. The monitored data indicated that the system mobilized -60 kPa atmospheric pressure. This allowed for unprecedented loading and settlement rates during the construction of an embankment and achieved the required degree of consolidation within the specified time period. The prediction by PVDCON FEM Software generally agreed with the observed values. As expected, increasing the Kh/Ks and OCR values resulted in lower settlement values.